(untitled) (Research, Society and Development, 2022)
The insertion of the family member/caregiver in the singular therapeutic project of patients in mental distress exposes us to rethink about a new care model for the production of mental health care, where the inclusion of this family in the project is not seen as the cause of the individual’s mental illness, but is relevant for the development of the patient’s treatment, strengthening their autonomy and social reintegration into the community. Therefore, the objective of this research was to map the articles of the databases, VHL and SciELO, existing in the Brazilian Literature on the insertion of the family member/caregiver in the therapeutic project of patients in psychological distress in the last ten years. The present study is an integrative review, following in the footsteps of Galvão et al. (2008), with the following guide question: "How does the insertion of the family member/caregiver in the therapeutic project of patients in psychological distress take place in the Brazilian literature?". The database selected for the study was SciELO (Scientific Library Online) and also the search in the Virtual Health Library (VHL), in which 17 articles were selected. From the clouds of words, their dimensions of access were analyzed, in which the family is essential in this therapeutic process assuming the responsibility of care with the user and the health team to promote the autonomy of the user, resuming their citizenship and social reintegration through the care of all.